2009
DOI: 10.1509/jmkg.73.5.103
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Value of Customization: When Do Customers Really Prefer Products Tailored to Their Preferences?

Abstract: Recently, researchers have paid increasing attention to the marketing strategy of customization. A key assumption is that customized products create higher benefits for customers than standard products because they deliver a closer preference fit. The prerequisite for this effect is the ability to obtain precise information on what customers actually want. But are customers able to specify their preferences that precisely? Several theoretical arguments raise doubts about this, implicitly challenging the value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
395
1
27

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 502 publications
(433 citation statements)
references
References 84 publications
(129 reference statements)
10
395
1
27
Order By: Relevance
“…For example, the degree of preference insight might moderate the benefits customers derive from MC due to the fact that customers with a low degree of preference insight might not be able to evaluate whether a product fits their preferences or not. Franke et al (2009) found that the effects of preference insight, the ability to express preferences, and product involvement on the benefit customers derive from customised products are moderated by the product category. The dissimilarity in the WTP for personalised scarves, T-shirts, or cell-phone covers, as mentioned above, illustrates that customers evaluate MC approaches differently.…”
Section: Relevant Factors Of the Mass Customised Product And The MC Pmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the degree of preference insight might moderate the benefits customers derive from MC due to the fact that customers with a low degree of preference insight might not be able to evaluate whether a product fits their preferences or not. Franke et al (2009) found that the effects of preference insight, the ability to express preferences, and product involvement on the benefit customers derive from customised products are moderated by the product category. The dissimilarity in the WTP for personalised scarves, T-shirts, or cell-phone covers, as mentioned above, illustrates that customers evaluate MC approaches differently.…”
Section: Relevant Factors Of the Mass Customised Product And The MC Pmentioning
confidence: 99%
“…Researchers have identified a number of product characteristics and, more recently, the MC process itself as an important value driving activity, which satisfies customers' hedonic needs. Various independent studies have found an increase in customers' WTP for mass customised products (e.g., Franke et al, 2009;Piller, 2004). However, the increase in the amount customers are willing to pay has been reported to be rather diverse.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations